Happy Valentine's Day, Curious George! - Di Angelo, N.; Young, Mary O'Keefe (Boston, Mass. : Houghton Mifflin Harcourt, 2010)
Curious George, the mischievous monkey, and his friends celebrate Valentine's Day with decorating, baking, card making, and some unexpected hilarity.
Cover title.
"With fold-out flaps!"--Cover.
Accelerated Reader AR
Keywords: Curious George (Fictitious character) -- Juvenile fiction; Valentine's Day -- Juvenile fiction; Parties -- Juvenile fiction